Microstructural and dielectric behaviour of glass ceramics in the system PbO-BaO-TiO2-B2O3-SiO2 - Parkash, O.M.; Kumar, D.; Rajgopalan, R. (Springer India, 1986)
Glasses in the system PbO-BaO-TiO2-B2O3-SiO2 with and without P2O5 as nucleant have been prepared. The glass samples were ceramized based on dta studies. The ferroelectric phase crystallizing out has been found to be BaTiO3 from xrd. The optical and scanning electron micrographs show the presence of BaTiO3 as major phase. In these glass ceramic samples, dielectric constant and dissipation factor are approximately constant with temperature and frequency upto the glass transition temperature T g and thereafter increase sharply with temperature and finally level off. The addition of P2O5 as nucleant and molar ratio of (PbO + BaO) to TiO2 has marked influence on the dielectric behaviour and composition of ferroelectric phase crystallizing out. © 1986 Indian Academy of Sciences.
Keywords: dielectric behaviour; differential thermal analysis; glass ceramic; Microstructure